Egocentric Spatial Representation in Action and Perception. - BRISCOE, ROBERT (Philosophy & Phenomenological Research, 2009)
Neuropsychological findings used to motivate the “two visual systems” hypothesis have been taken to endanger a pair of widely accepted claims about spatial representation in conscious visual experience. The first is the claim that visual experience represents 3-D space around the perceiver using an egocentric frame of reference. The second is the claim that there is a constitutive link between the spatial contents of visual experience and the perceiver’s bodily actions. In this paper, I review and assess three main sources of evidence for the two visual systems hypothesis. I argue that the best interpretation of the evidence is in fact consistent with both claims. I conclude with some brief remarks on the relation between visual consciousness and rational agency.